SOFC's Anode Protection by Bias Current Application: First Experimental Results on a Short Stack. Issue 5 (6th September 2017) - Brunaccini, G.; Ferraro, M.; Squadrito, G.; Di Giovanni, L.; Antonucci, V.
Abstract: Solid oxide fuel cells (SOFCs) are exposed to failures due to thermal and redox cycles, above all in the case of unexpected shut downs. Effects of thermal cycles related to controlled startup and shutdown can be mitigated by appropriate start/stop strategies, but unpredictable shutdowns strongly damage the devices, especially in anode supported cells. On the one hand, the nickel oxidation quickly arises above 250 °C at the anode and usually leads to cells cracks; on the other hand, very fast cooling of the SOFC stack down to 250 °C could lead to the thermal shock breakage as a consequence. Recently, reverse bias current application has been proposed to protect the anode from re‐oxidation. In the presented work, the reverse bias current approach has been applied on a SOFC stack to assess the technique for relevant power devices. The results show that this protection method is promising as a safety approach.